Hydroponics and elicitation, a combined approach to enhance the production of designer secondary medicinal metabolites in Silybum marianum - Mubeen, Bismillah; Hasnain, Ammarah; Mehboob, Riffat; Rasool, Rabia; Riaz, Ayesha; Elaskary, Shymaa Abdelsattar; Shah, Muhammad Muntazir; Faridi, Tallat Anwar; Ullah, Inam (Frontiers in Plant Science, 2022)
Medicinal plants have been used to cure human diseases since decades. Silybum marianum, a medicinal plant, is regarded as a source of secondary metabolites with therapeutic values against liver diseases, de-toxification and diabetes. The present study was conducted to enrich the production of secondary metabo-lites in the vegetative parts of Silybum marianum using elicitation technique in hydroponic system with different elicitors. The elicitors of fungus Aspergillus niger (0.2g/L), methyl jasmonate (MeJA) (100µM/L) and silver nanoparticles (AgNPs) (1 ppm/L) were added in hydroponic medium, individually and in combination form to the 15 days old plant. The experiment was conducted using Completely Ran-domized Design (CRD) in five replicates. Plants were harvested after an interval of 24 hours viz. 24 hours, 48 hours, 72 hours, 96 hours, 120 hours and 144 hours. Biochemical parameters including phenolics, fla-vonoids, nitric oxide (NO) and superoxide dismutase (SOD) were then analyzed and the results shows an increased production of these parameters by the elicitors and among these elicitors, MeJA proved to have the highest efficacy followed by AgNPs, fungal elicitors and the combinations of MeJA and AgNPs. Our findings depicted an enhanced production of medicinally important plant secondary metabolites and anti-oxidants hence, the method applied in this study can play a significant role to improve the therapeutic val-ues of the plants.